How Adversity Quotient and Learning Independence Affect Students' Mathematical Problem-Solving Ability - Gabariela Purnama Ningsi; Dwi Juniati; Siti Khabibah (Universitas Islam Lamongan, 2025)
This study aims to analyze the influence of Adversity Quotient (AQ) and learning independence on students' mathematical problem-solving abilities and to explore problem-solving strategies based on differences in AQ and learning independence levels. The study employed a mixed-methods approach with a sequential explanatory design, involving 150 secondary school students. Results showed that AQ and learning independence significantly influenced problem-solving abilities, with learning independence having a greater impact. Students with high learning independence were more innovative and persistent, while those with low independence faced challenges. This study highlights the importance of developing AQ and learning independence to enhance students' problem-solving skills. Education should strengthen these aspects through strategies like project-based learning and resilience training, to better prepare students for real-world challenges.